Pengaruh Pemberian Formula Kue Semprit Terhadap Kadar Hemoglobin pada Remaja Putri Anemia di SMAN 19 Palembang - Rain, Srirekha Mutiasyah; Yulianto, Yulianto; Siregar, Afriyana (Universitas Islam Negeri Walisongo Semarang, 2024)
This research to determine the effect of giving semprit cake with the addition of chicken liver and soy bean flour on Hb levels in anemic adolescent girls at SMA Negeri 19 Palembang. This research is a quasi-experimental research. Providing food in the form of semprit cake with the addition of chicken liver and soy bean flour to adolescent girls for 30 consecutive days, as many as 8 pieces of semprit cake per day. Samples in this study were taken using simple random sampling technique. It was found that most respondents were 15 years old (56.7%) out of 30 respondents in the treatment group and 15 years old (46.7%) out of 30 respondents in the comparison group. The average increase in hemoglobin was 3.503 g/dl in the treatment group and 0.004 g/dl in the comparison group. The results of the t-dependent statistical test in the treatment group obtained a p-value <0.05 (0.000) and in the comparison group obtained a p-value >0.005 (0.000). The t-independent test obtained a p-value <0.05 (0.000). It is concluded that there is an effect of semprit cake with the addition of chicken liver and soy bean flour on increasing hemoglobin levels of anemic adolescent girls at SMA Negeri 19 Palembang. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian kue semprit dengan penambahan hati ayam dan tepung kacang kedelai terhadap kadar Hb pada remaja putri anemia di SMA Negeri 19 Palembang. Penelitian ini adalah penelitian eksperimen semu (quasi eksperimen). Pemberian makanan dalam bentuk snack kue semprit dengan penambahan hati ayam dan tepung kacang kedelai kepada remaja putri selama 30 hari berturut-turut sebanyak 8 keping kue semprit per hari. Sampel pada penelitian ini diambil dengan teknik simple random sampling. Responden sebagian besar berusia 15 tahun (56,7%) dari 30 responden pada kelompok perlakuan dan berusia 15 tahun (46,7%) dari 30 responden pada kelompok pembanding. Rata-rata peningkatan hemoglobin adalah 3,503 g/dl pada kelompok perlakuan dan 0,004 g/dl pada kelompok pembanding. Hasil uji statistik t-dependent pada kelompok perlakuan didapatkan nilai p-value <0,05 (p<0,001) dan pada kelompok pembanding didapatkan nilai p-value>0,005 (p=0,967). Uji t-independent didapatkan nilai p-value <0,05 (p<0,001). Disimpulkan bahwa ada pengaruh pemberian kue semprit dengan penambahan hati ayam dan tepung kacang kedelai terhadap peningkatan kadar hemoglobin remaja putri anemia di SMA Negeri 19 Palembang.